Production of Z0 and in relativistic heavy-ion collisions at the LHC. (18th June 2015) - Ru, Peng; Zhang, Ben-Wei; Cheng, Luan; Wang, Enke; Zhang, Wei-Ning
Abstract: The production of massive gauge bosons, Z 0 and, in heavy-ion reactions at the Large Hadron Collider (LHC) provides an excellent tool for studying cold nuclear matter effects in high-energy nuclear collisions. In this paper we investigate Z 0 and production in p+Pb and Pb+Pb at the LHC, at next-to-leading order and next-to-next-to-leading order, using the DYNNLO program and incorporating the nuclear parton distribution function (nPDFs) parametrization sets EPS09 and DSSZ, within the framework of perturbative quantum chromodynamics. Numerical simulations of the transverse momentum spectra, rapidity dependence and related nuclear modification factors for Z 0 and W particles, as well as the charge asymmetry for the W boson, are provided and tested against the latest experimental data. It is found that the theoretical results with EPS09 and DSSZ nPDFs can provide good descriptions of the recent data on Z 0 and particles in p+Pb and Pb+Pb within the experimental error bars, although some differences between the results with EPS09 and DSSZ can be observed, especially in the rapidity dependence of the Z 0 yield. Theoretical predictions for future measurements on Z 0 and W in p+Pb and Pb+Pb collisions at the LHC are also provided.